If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3p(p + 5) = 0 Reorder the terms: 3p(5 + p) = 0 (5 * 3p + p * 3p) = 0 (15p + 3p2) = 0 Solving 15p + 3p2 = 0 Solving for variable 'p'. Factor out the Greatest Common Factor (GCF), '3p'. 3p(5 + p) = 0 Ignore the factor 3.Subproblem 1
Set the factor 'p' equal to zero and attempt to solve: Simplifying p = 0 Solving p = 0 Move all terms containing p to the left, all other terms to the right. Simplifying p = 0Subproblem 2
Set the factor '(5 + p)' equal to zero and attempt to solve: Simplifying 5 + p = 0 Solving 5 + p = 0 Move all terms containing p to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + p = 0 + -5 Combine like terms: 5 + -5 = 0 0 + p = 0 + -5 p = 0 + -5 Combine like terms: 0 + -5 = -5 p = -5 Simplifying p = -5Solution
p = {0, -5}
| 1-3m=1-7m | | 7ex=14 | | 2(x-4)+3x=12 | | 7x-(2x-4)=19 | | 7(4x+6)=-6(1-6x) | | 12.5y=225 | | 6(5p+8)=4(4+8p) | | x^2+13+42= | | 13+8x=x+6 | | 3x^2+30x=72 | | 15x^5-2x^3=24 | | 7x+1=-11+4x | | -x=0.75 | | B(t)=10et | | 11+8x=10x-3 | | -3(1+4p)=69 | | 3x(a-2b)+3b= | | -124=-2p+4(2-5p) | | 8a+3=6a+2 | | -124=2p+4(2-5p) | | 20=5b+8-b | | 2b+7b=9 | | 7u+49=-5u+25 | | X^2y-3xy^2-6x^2y= | | x+2/5+x=2/3 | | 8x-4+3x=8x+14 | | a^2+2a-1=0 | | 11=-13y+3y | | -3y+4+6y= | | 6m+x=24 | | 2m-3=6m-4 | | 8(n-1)=-32 |